Enhancing the impact of natural resource management research: Lessons from a meta-impact assessment of the Irrigated Rice Research Consortium - Roderick M. Rejesus (2018)
This article present results from a multi-dimensional impact assessment of a large multi-year Natural Resource Management (NRM) research project for rice - the Irrigated Rice Research Consortium (IRRC) - and uses insights from this assessment to further understand how NRM research can be improved to have more impact in a developing country context. Results of the meta-impact assessment indicate that NRM research generated by the IRRC has provided a wide-range of impacts in multiple dimensions-from micro-level impacts on farmer livelihoods to national-level agricultural policy influence. Based on the IRRC experience, international NRM research institutions can enhance impact in developing countries by: fostering partnerships, collaborations, and cross-country learning; involving social scientists for monitoring, evaluation, and impact assessment; and, having long-term support and involvement of donors. © 2013 Elsevier B.V.